Pure honey and health awareness: Unveiling the drivers of muslim consumer behavior - Qultsum, Kholilah; Gayatri, Gita (The Journal of Religion and Communication Studies, 2025)
Background: The increasing awareness of health among consumers has led to a growing interest in natural products such as pure honey. Particularly among Muslim consumers, the decision to consume pure honey is often influenced by beliefs regarding its health benefits. Methods: This study employed a quantitative approach using survey data collected from Muslim consumers. A total of 300 respondents were analyzed to understand the relationship between health awareness and the consumption of pure honey. The study utilized statistical analysis to examine the impact of health awareness on consumers’ attitudes, reasons for consumption, and reasons for non-consumption. Additionally, a mediation analysis was conducted to explore the role of consumption reasons in the relationship between health awareness and attitudes. Findings: The results indicated that health awareness positively influenced consumers' attitudes toward pure honey and their reasons for consuming it. However, health awareness did not significantly affect reasons for non-consumption. The reason for consumption acted as a partial mediator in the relationship between health awareness and attitudes. Consumers with high health awareness were more likely to believe in the benefits of pure honey and were less concerned about doubts regarding the product’s authenticity. Over half of the respondents identified health as the primary motivation for consuming pure honey, with regular consumption observed among the majority. Conclusion: This study emphasizes the significant role of health awareness in shaping the consumption behavior of pure honey among Muslim consumers. Health awareness positively influences consumers' attitudes and motivations to consume pure honey, highlighting the importance of transparency and product certification in marketing. Businesses in the pure honey industry can enhance consumer trust and market position by focusing on the health benefits and authenticity of their products. Novelty/Originality of this article:  It provides novel insights into the mediating role of consumption motivations in the relationship between health awareness and product attitudes, offering practical implications for marketing strategies in the health-conscious consumer market.